2001
DOI: 10.1016/s1097-2765(01)00149-6
|View full text |Cite
|
Sign up to set email alerts
|

Composite Active Site of an ABC ATPase

Abstract: The MutS protein initiates DNA mismatch repair by recognizing mispaired and unpaired bases embedded in duplex DNA and activating endo- and exonucleases to remove the mismatch. Members of the MutS family also possess a conserved ATPase activity that belongs to the ATP binding cassette (ABC) superfamily. Here we report the crystal structure of a ternary complex of MutS-DNA-ADP and assays of initiation of mismatch repair in conjunction with perturbation of the composite ATPase active site by mutagenesis. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
148
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(163 citation statements)
references
References 44 publications
14
148
1
Order By: Relevance
“…Sliding of any more elaborate complex past a stiff hairpin extending about 70 Å from a 20-Å diameter helix would seem unlikely, virtually impossible if the complex included PCNA, whose central hole is 34 Å in diameter (27). Our data clearly do not falsify the hypothesis of Hsieh co-workers (9,10), that mismatch-activated searching complexes, containing hMutS␣, MutL␣, and perhaps other proteins, might remain at or near the mismatch and search for the nick through space.…”
Section: Fig 2 Mmr Substratescontrasting
confidence: 41%
See 2 more Smart Citations
“…Sliding of any more elaborate complex past a stiff hairpin extending about 70 Å from a 20-Å diameter helix would seem unlikely, virtually impossible if the complex included PCNA, whose central hole is 34 Å in diameter (27). Our data clearly do not falsify the hypothesis of Hsieh co-workers (9,10), that mismatch-activated searching complexes, containing hMutS␣, MutL␣, and perhaps other proteins, might remain at or near the mismatch and search for the nick through space.…”
Section: Fig 2 Mmr Substratescontrasting
confidence: 41%
“…In these cases, PCNA might play two roles even before DNA resynthesis: (i) tethering MutS␣ to homoduplex DNA via the known MutS␣⅐PCNA interactions, but releasing it when a mismatch is encountered, thus enhancing the efficiency of mismatch recognition, as suggested by other work (26), and (ii) allowing more elaborate recognition complexes, perhaps involving as well MutL␣, excision factors, and PCNA itself, to slide toward excision-initiation sites (25). We find here that purified hMutS␣ alone, apparently in contrast to bacterial MutS protein (9), is not retained on mismatched DNA blocked at both ends with hairpins in the presence of ATP. Thus, our experiments do not falsify any hypothesis in which ATP-dependent sliding of MutS␣ alone, either directly from a mismatch or after a cycle of MutL␣ recruitment and release by PCNA, searches for the excision-initiation signal, but do demand that the mode of any such sliding be loose enough to permit movement past the hairpin.…”
Section: Fig 2 Mmr Substratesmentioning
confidence: 53%
See 1 more Smart Citation
“…Both contain Walker A and B consensus sequences as well as the highly conserved 'LS-GGQ' signature sequence or C-motif. In DNA mismatch repair, the MutS ABC ATPase uses ATP binding to recognize and bind misrepaired DNA (Junop et al, 2001). In double-stranded break repair, Rad50 uses ATP to bind and bridge DNA double-strand breaks (Chen et al, 2001;Lobachev et al, 2002), and ABC transporters use the energy from ATP hydrolysis to transport substances across membranes (Hyde et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…One invokes movement of MutS or the MutL-MutS complex along the helix between the mismatch and the strand signal (11-13), a second posits mismatch recognition by MutS as a trigger for polymerization of a second protein along the helix between the two DNA sites (11), and the third attributes interaction of the two sites to a DNA-looping mechanism (14,15). Several laboratories have demonstrated that, when challenged with ATP, MutS homologs leave a mismatch by movement along the helix contour, and evidence for movement of the MutL-MutS homolog complex along DNA also is available (reviewed in refs.…”
mentioning
confidence: 99%